Tension modulates actin filament polymerization mediated by formin and profilin - Courtemanche, Naomi (National Academy of Sciences, 2013)
Formins promote processive elongation of actin filaments for cytokinetic contractile rings and other cellular structures. In vivo, these structures are exposed to tension, but the effect of tension on these processes was unknown. Here we used single-molecule imaging to investigate the effects of tension on actin polymerization mediated by yeast formin Bni1p. Small forces on the filaments dramatically slowed formin-mediated polymerization in the absence of profilin, but resulted in faster polymerization in the presence of profilin. We propose that force shifts the conformational equilibrium of the end of a filament associated with formin homology 2 domains toward the closed state that precludes polymerization, but that profilin–actin associated with formin homology 1 domains reverses this effect. Thus, physical forces strongly influence actin assembly by formin Bni1p.